Readiness of PSMZA Lecturer on The Use of Mooc Platform in Learning and Teaching - Hasliza Binti Hashim; Pazlina Binti Mat Ali (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Currently, Malaysia is faced with challenges in efforts to provide a quality educational system. One of the surge in the Development Plan of Education (higher education) 2015-2025 is to ensure learning online at global level. So with this, the use of platform MOOC is one the first method was introduced as one of the approaches in learning and teaching. However the question arises whether polytechnic lecturer was ready to use online learning extensively, particularly in the process of learning and teaching. This study is intended to review the availability of committed lecturers Politeknik Sultan Mizan Zainal Abidin of the use of platform MOOC in learning and teaching. Respondents were 153 lecturers in PSMZA and it has been selected at random. The instruments used are a set of survey questions. The findings indicate the availability of lecturers PSMZA will against the use of platform MOOC in learning and teaching are not influenced by gender. The mean score for female lecturers was 2.83 compared mean score men namely 2.57 and this shows women more ready against the use of platform MOOC. The mean score for aspects of female lecturers obstacles higher than male lecturers. This suggests that female lecturers more willing to use MOOC in learning and teaching although there are some aspects which have become obstacles. Someone who had the expectation of high availability using MOOC are less face obstacles while using MOOC in learning and teaching sessions. Coefficient of correlation variables obstacles in the use of MOOC and graduate readiness against MOOC is very weak with the value of the coefficient of correlation of -0.078. It is mean that female lecturers more willing to use MOOC in learning and teaching although there are some aspects which have become obstacles. Therefore clearly showed the use of MOOC among the lecturers PSMZA will provide positive indicators and should be polished to ensure the integration of technology in education achieved towards helping towards the Industrial Revolution 4.0.